Pengembangan Modul Berbasis Problem Based Learning pada Materi Kesetimbangan Kimia untuk Kelas XI SMA/MA - Tiara Tamita; Ellizar Ellizar (Entalpi Pendidikan Kimia, 2021)
ABSTRACTChemical equilibrium is part of material studied in odd semester of 2nd grade Senior High School. One of the learning models used to study this material is the Problem Based Learning. This development research aims to produce and determine its validity category of modules. This research was a Research and Development (R&D) using the plomp model developed by Tjer Plomp. This model consists of 3 main stages, (1)Preliminary Stage ; (2) Prototyping Stage; (3) Asessment Phase. This research was limited to Prototyping Stage of validity test. The research instrument was a validity questionnaire given to two lecturers from Department of Chemistry, of FMIPA UNP and two chemistry teachers at SMA Negeri 3 Padang. The Analysis showed that the modules was very valid with a value of 0,81. Keywords:Chemical Equilibrium, Model Plomp, Modules, Problem Based Learning,Validity